Occurrence of E. coli O157 H7 from meat products sold in Obinze abattoir, IMO State, Nigeria - Osazee Ekundayo Izevbuwa; Shadrach Osalumhense Okhuebor (Hasanuddin University, 2020)
AbstractThis survey was carried out to investigate the occurrence of Escherichia coli O157:H7 in meat products from Obinze abattoir, Imo state, South-Eastern Nigeria. A total of 10 beef samples, 10 processing water samples, 10 table swabs and 20 entrails samples were collected. Pour plate technique was used after a tenfold serial dilution to inoculate on Eosin Methylene Blue (EMB) agar and the E. coli isolates were cultured on Sorbitol MacConkey agar and incubated for 24 hours at 37oC. The isolates were subjected to biochemical tests for identification before antibiotic sensitivity test was carried out using the disc diffusion (Kirby-Bauer) method. From the survey, the entrails had the highest rate of isolation (4.16 ±0.56 log10 Cfu/ml) followed by the beef samples with (3.58 ± 0.01 log10 Cfu/ml). The processing water and the table swabs yielded no growth of E. coli O157:H7. The percentage occurrence of E. coli O157:H7 was also determined and the entrails samples had the highest with (17, 89.5%) followed by the beef samples with (2, 10.5%). The processing water and table swabs samples did not yield growth of E. coli O157:H7 and their percentages were 0. The data obtained were subjected to statistical analysis using the single sample T test which showed that there was no significant difference (p > 0.05) in the rate of isolation of E. coli O157:H7 from the samples. The E. coli O157:H7 isolated showed 100% sensitivity to all the antibiotics used. The presence of E. coli O157:H7 implies that these food samples from the Obinze abattoir, if consumed could be a potential public health hazard to the community. Therefore, strict adherence to quality control measures should be implored in order to reduce contamination and food borne illnesses.Keywords: Escherichia coli O157:H7, public health, hazard, contamination, occurrence